2018
DOI: 10.1007/s00132-017-3522-3
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent intervertebral space infection after lumbar fusion

Abstract: Adjacent level infections can occur after spinal surgery. Early diagnosis and anti-infection treatment played an important role in the treatment of this kind of complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…ASI after surgery of spondylodiscitis is considered as a rare complication (1.94%) via a large cohort study [2]. ASI in uninfected spinal surgery should be rarer, and in fact, only four case reports introduced it in conventional spinal fusion surgery [3][4][5][6]. In this present case, the patient developed ASI two months after the initial instrumented lumbar fusion surgery and achieved satisfactory outcome via debridement operation and autograft bone implantation fusion after failed conservative treatment.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…ASI after surgery of spondylodiscitis is considered as a rare complication (1.94%) via a large cohort study [2]. ASI in uninfected spinal surgery should be rarer, and in fact, only four case reports introduced it in conventional spinal fusion surgery [3][4][5][6]. In this present case, the patient developed ASI two months after the initial instrumented lumbar fusion surgery and achieved satisfactory outcome via debridement operation and autograft bone implantation fusion after failed conservative treatment.…”
Section: Introductionmentioning
confidence: 63%
“…Nagoshi et al [6] reported three ASI cases which involved T11-12, L1-2, and L2-3. A case reported by Xin and He [5] occurred at level L3-4. Formica et al [7] and Lange et al [4] reported two ASI cases which occurred in the thoracic spine.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations